Amino acid composition, antioxidant property and Angiotensin I-Converting Enzyme (ACE) inhibitory activity of micropeptides in skim milk powder. - Cui, Lei; Huang, Mini; Zhao, Daxian; Deng, Yun; Qian, Bingjun; Zhang, Li; Luo, Yali; Qingxiao, Wu; Wu, Mengzhang (2011)
The study evaluated the amino acid composition, and the antioxidant and antihypertensive characteristics of micropeptides in skim milk powder. Milk proteins were slightly destroyed during the production of skim milk powder based on results of sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The skim milk powder was rehydrated and salted-out. After centrifugation, the supernatants were subjected to microfiltration and then separated with Superdex-30G column fractionation, producing three fractions (PF-I, PF-II and PF-III). The molecular weight of fraction PF-III was about 1.0 kDa with a yield of 10.9 ± 0.73 mg g -1 skim milk powder. Fraction PF-III at 10 mg mL-1 showed modest antioxidant activity with a 1.1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging rate of 36.69 ± 0.92%. The inhibitiory rate of the angiotensin I-converting enzyme (ACE) activity of PF-III at a concentration of 3 mg mL -1 was about 20.12 ± 7.59%. Fraction PF-III was found to be rich in Gly, Phe, Leu, Glu and Asp, and its total hydrophobic amino acid content was as high as 50.53%, which may have contributed to the antioxidant and ACE-inhibitory activities.
Keywords: Milk -- Composition